Evolutionary algorithms for solving multi-objetive problems. Carlos A. Coello Coello, David A. van Veldhuizen and Gary R., Lamont : Kluwer Academic/Plenum Publishers, New York, first edition, 2002 - Esquivel, Susana Cecilia (2002)
In this book the authors present a complete state-of-the art in the field. Then they give an overall vision about the diverse varieties of MOEAs (Multi-Objetive Evolutionary Algorithms) and their performance. Important aspect such as selection and validation of function tests, MOEA comparison metrics and presentations techniques are also analized. The last two chapters describe theoretical and parallelization issues of this algorithhm class.